The effect of prenatal education on fear of childbirth, pain intensity during labour and childbirth experience: a scoping review using systematic approach and meta-analysis - Zohreh Alizadeh-Dibazari; Somayeh Abdolalipour; Mojgan Mirghafourvand (BMC, 2023)
Abstract Background Antenatal education provides parents with strategies for pregnancy, childbirth, and parenthood. There is not enough evidence of the positive effect of prenatal education on childbirth and maternal outcomes. The present scoping review using a systematic approach, evaluates the effectiveness of prenatal education on fear of childbirth, pain intensity during labour, childbirth experience, and postpartum psychological health. Methods We used Google Scholar and systematically reviewed databases such as PubMed, Web of Science, Cochrane, Scopus, and SID (Scientific Information Database). Randomized controlled and quasi-experimental trials examining the effect of structured antenatal education and routine prenatal care compared to routine prenatal care were reviewed. The participants included pregnant women preferring a normal vaginal delivery and had no history of maternal or foetal problems. The outcomes considered in this study included fear of childbirth, pain intensity during labour, childbirth experience (as primary outcomes) and postpartum psychological health (as secondary outcomes). The grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to evaluate the quality of evidence. Results Overall, 3242 studies were examined, of which 18 were qualified for the final analysis. The meta-analysis showed that providing prenatal education and routine care compared to only routine care may decrease the fear of childbirth, postpartum depression, and pain intensity during labour. However, we found no study examining the outcome of the childbirth experience. In addition, the inconsistency of included studies prevented conducting a meta-analysis on the rest of the outcomes. Conclusions Our investigations showed that there are very few or no studies on the effect of prenatal education on outcomes such as childbirth experience, postpartum anxiety, and maternal attachment, and the existing studies on the effect of prenatal education on outcomes such as the fear of childbirth, postpartum depression, and pain intensity during labour lack sufficient quality to make definitive conclusions. Therefore, high-quality, randomized trials with a more extensive sample size are suggested to provide clear reports to make definitive decisions. Prospero ID CRD42022376895.